Independent Learning Curriculum in School Education Concepts and Planning in Islamic Religious Education Perspective - Ria Mutiani; Ainun Mardiah (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2022)
This study tries to describe and analyze the importance of the